THE SENIOR STUDENT'S VIEW OF PHYSICAL ACTIVITY IN THE AGEING PROCESS - Firmino, Cristiana Furtado (2025)
Physical activity in the elderly is associated with a reduction in the adverse effects of the ageing process, with various physical, mental, social, psychological, and spiritual benefits. The results of attending a senior university with physical activity are unquestionable in terms of promoting active ageing. The aim of this study was to understand how senior students perceive the role of physical activity in their ageing process. The methodology adopted was a qualitative, descriptive study, using the Focus Group method and technique with seven elderly students who attend senior university. The Bardin protocol was followed for data processing and analysis. All the ethical procedures required for this study were complied with. The main results show that there are representations related to physical activity (satisfaction, commitment, importance, and stimulation) that make these students feel that physical activity improves their functional capacity and promotes their well-being. In terms of personal development, physical activity improves their confidence and makes them aware of the frailties of old age. It should also be noted that the motivations for attending senior university emerge from the experience of new experiences, new learning, and knowledge, that the activities offered are suited to the needs of each student, as well as the practice of physical activity being adapted to each physical condition, which is undoubtedly a great motivation to continue attending this space.  This research is in line with current literature and scientific evidence, contributing to conscious decision-making in clinical nursing practice about the elderly, who should be seen as active, with goals and life projects.